Prospects for Digitalization of ASEAN Smart Cities Network Securitization: Case Studies Indonesia - Fathun, Laode Muhammad (WIMAYA, 2023)
This paper aims to explain the opportunities and challenges of securitization in the digitization of ASCN. This paper uses qualitative methods with case study methods and uses library review data collection techniques. The results found that the digitalization of ASCN is a form of ASEAN's commitment to innovate and digital transformation of both the government, society and the business world. ASCN is a concrete form of public service governance to create connections and integration between cities in ASEAN so that they can collaborate and synergize. However, from this cooperation, there are a number of opportunities and challenges that can be obtained by ASEAN. This means that ASCN cooperation must be well controlled because the city is a major player in the cooperation even though the agreement is at the national and regional levels.